2015
DOI: 10.1186/s12941-015-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum adequacy of antibiotic regimens for secondary peritonitis: a retrospective analysis in intermediate and intensive care unit patients

Abstract: Background Secondary peritonitis requires surgical source control and adequate antimicrobial treatment. Antimicrobial regimens are usually selected according to local susceptibility data of individual pathogens against single agents, but this neglects both the polymicrobial nature of the infection and the use of combination therapy. We analysed the probability of common regimens to cover all relevant pathogens isolated in one patient (“spectrum adequacy rate”, SAR) in a real-life data set.Methods Data from 242… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
0
16
0
3
Order By: Relevance
“…( 9 , 10 ) However, MDR is also increasing in community-acquired infections, with extended-spectrum beta-lactamase (ESBL)-producing bacteria being the most globally widespread problem, although there is important regional variation in its prevalence. ( 11 , 12 ) In nosocomial infections, ( 4 , 9 , 13 ) both Gram-positive and Gram-negative pathogens that have MDR may be encountered, and these include methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE) and ESBL-producing Enterobacteraceae but also carbapenem-resistant Enterobacteraceae (CRE), MDR Pseudomonas aeruginosa and Acinetobacter spp., which also have important geographical variations.…”
Section: Multidrug Resistance Is a Pressing Issue Also In Peritonitimentioning
confidence: 99%
“…( 9 , 10 ) However, MDR is also increasing in community-acquired infections, with extended-spectrum beta-lactamase (ESBL)-producing bacteria being the most globally widespread problem, although there is important regional variation in its prevalence. ( 11 , 12 ) In nosocomial infections, ( 4 , 9 , 13 ) both Gram-positive and Gram-negative pathogens that have MDR may be encountered, and these include methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE) and ESBL-producing Enterobacteraceae but also carbapenem-resistant Enterobacteraceae (CRE), MDR Pseudomonas aeruginosa and Acinetobacter spp., which also have important geographical variations.…”
Section: Multidrug Resistance Is a Pressing Issue Also In Peritonitimentioning
confidence: 99%
“…Typhimurium, H. alvei and E. cloacae; all responsible for nosocomial infections that can lead to lifethreatening bacteremia (Alexopoulou et al, 2016;Kim et al, 2015;Steinbach, Töpper, Adam, & Kees, 2015).…”
Section: Results and Discussion 31 Release From Aerogels And Activitmentioning
confidence: 99%
“…A similar experiment was carried out on a strain of S. marcescens, a species recognized to cause human clinical diseases, with a multidrug-resistance profile (Zavascki, Goldani, Li & Nation, 2007). Following the same protocol as above, we have evaluated four other Gram-negative bacterial species involved in nosocomial infections, that can be fatal, mostly if infected patients are elderly, young, or people with depressed immune systems (Alexopoulou et al, 2016;Kim et al, 2015;Steinbach et al, 2015). The bacterial strains were the following: S. Typhimurium (Fig.…”
Section: S In "Supplementarymentioning
confidence: 99%
“…Since Enterococci are resistant to many antibiotics and Meropenem is only of limited effectiveness, therapy with Tigecycline or Piperacillin/Sulbactam should be considered if Enterococci are revealed in the culture. In previous studies, Tigecycline in combination with Gentamicin or Ciprofloxacin was found to be effective against Enterobacteriaceae 29 .…”
Section: Discussionmentioning
confidence: 96%